(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Enterohemorrhagic Escherichia coli O157 is a widespread foodborne pathogen that causes severe illness in humans globally. In the United States, the most common sources of disease outbreaks are bovine food products and fresh produce contaminated with bovine feces, as healthy cattle serve as a reservoir for E. coli O157. This bacterium is also resilient in the environment, capable of surviving in diverse conditions. To cause human illness, colonize the bovine gastrointestinal system, and persist in the environment, E. coli O157 must adapt to various environments. Important virulence factors of E. coli O157 include Shiga toxins, products of the pathogenicity island known as the locus of enterocyte effacement, and products of the F-like plasmid pO157. Among these, pO157 plays a significant role, though it is the least understood of the virulence factors. This article provides a general overview of E. coli O157, with a particular emphasis on pO157.